Researching global citizenship education: Towards a critical approach - Schippling, Anne (JSSE - Journal of Social Science Education, 2020)
Purpose: This article contains a reflection on researching in global citizenship education with a critical approach that aims to transcend the paradigm of methodological nationalism. Design/methodology/approach: Starting from outlining different dimensions of global citizenship (education), and looking at the current research situation in GCE, we propose a methodological turn that overcomes the nation-state paradigm as a base for critical research on GCE. Subsequently, using the concept of transnational capital as an analytical tool, we show – in the example of two biographical case studies in an international school in a large city of West Germany – how to put a critical research on GCE into action. Findings: The article demonstrates, on the one hand, how a critical approach to research aspects of global citizenship education can be taken, starting from a transnational research stance. On the other hand, it presents new perspectives and challenges for critical research in GCE.